Ibn ‘Āshūr and Negation of Minority’s Contribution To the Development of Nation - Saifuddin Herlambang; Budi Juliandi (Ulumuna, 2018)
The Quran promotes universal values. However, the interpretation of the Quran may potentially reduce its universality. This paper presents the concept of shūrā and sadaqa in al-Taḥrīr wa al-Tanwīr authored by Ibn ‘Āshūr, focusing on Surah Āli ‘Imrān (3): 159 and Surah al-Baqarah (2): 264. It also brings up other interpretations to provide a variety of opinions from Muslim scholars. This study builds up on the Malasevic’s theory of identity politics, stating that identity politics is not only exercised by marginalized people, or minorities in the midst of a major power within a country, but also in the majority, as well as in the ruling group. This study argues that Ibn ‘Āshūr’s interpretation is influenced by Islamic identity politics that negate other identities. He therefore excludes non-Muslims’ engagement in the process of national consolidation and development in Tunisia. This paper further maintains that, unlike Ibn ‘Āshūr’, the interpretation of the concept of shūrā should yield a peaceful coexistence between minorities and majorities in Muslim countries and beyond.